Revolutionizing Children's English Vocabulary Acquisition: The Power of Educational Games - Aprilia, Fitria; Neisya, Neisya; Rizkiani, Alni Ayu (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Language learners' proficiency heavily relies on their grasp of English vocabulary. Proficiency in vocabulary corresponds to improve language skills. This research delves into the profound impact of educational games on English vocabulary acquisition, shedding light on the positive influence these games wield on children's linguistic development. Employing a descriptive qualitative case study approach rooted in Skinner's theory, this research extracts data through direct observation. The subsequent analysis involves a series of steps: identifying words acquired by children from the educational game "My Talking Tom," categorizing the amassed vocabulary, juxtaposing the data, transcribing children's pronunciation of the vocabulary, and ultimately drawing insightful conclusions. The findings of this investigation unveil a notable surge in vocabulary acquisition attributable to the "My Talking Tom" game, underscoring its favorable influence on children.